Time-Dependent Semidiscrete Analysis of the Viscoelastic Fluid Flow Problem Using a Variational Multiscale Stabilized Formulation - Castillo-Del Barrio, E (Oxford University Press, 2019)
In this article we analyse a stabilized finite element formulation recently proposed to approximate viscoelastic fluid flows. The formulation has shown to have accuracy and robustness in the different benchmarks tested in the viscoelastic framework, and permitting the use of equal interpolation of the unknown fields. We first present results about a linearized subproblem, for which well-posedness and stability results can be proved. Then, the semidiscrete nonlinear time-dependent case is addressed using a fixed point theorem, which allows us to prove existence of a semidiscrete solution, along with error estimates. © 2018 The Author(s). All rights reserved.